Acidocalcisomes: conserved from bacterial to human cells - Docampo, Roberto (Henry Stewart Talks, 2012)
Acidocalcisomes and other acidic calcium stores, History of Acidocalcisomes, Morphological characteristics, Chemical compositions, Distribution in different species and functions